Le calcul de La Poste faisant foi - Nicolas Jounin (La Nouvelle Revue du Travail)
La Poste (France’s main state-owned postal service) determines its workers’ delivery routes by estimating how long it takes to sort and deliver people’s mail. Until the early 2000s, this was done by timing each route using a stop-watch. Due to falling postal mail volumes from the mid-2000s onwards, La Poste began increasing the frequency of delivery routes’ automatic re-evaluations, which now combined factors including traffic estimates, geographic data and pre-determined speed and time standards. The idea was that this would lead to a more objective calculation of workloads. In reality, working conditions have deteriorated significantly. Standards, for instance, have not changed for more than twenty years now, even though the conditions underpinning their creation no longer exist. The same applies to the legal employment regime that had validated them at first. The practice of allowing postal delivery staff to go home once they have completed their daily routes – an approach that had enabled the organization of work to be calculated using statistical averages – may work for most public sector officials. But it is at odds with France’s general labour laws, being the framework that applies nowadays to almost all postal delivery staff.